Crystallization and preliminary X‐ray diffraction analysis of the complex between a human anti‐alpha toxin antibody fragment and alpha toxin. Issue 3 (24th March 2013) - Oganesyan, Vaheh; Barnes, Arnita; Tkaczyk, Christine; Ferguson, Andrew; Wu, Herren; Dall'Acqua, William F.
<x xml:space="preserve">Abstract</x> Staphylococcus aureus alpha toxin (AT) has been crystallized in complex with the Fab fragment of a human antibody (MEDI4893). This constitutes the first reported crystals of AT bound to an antibody. The monoclinic crystals belonged to space group P21, with unit‐cell parameters a = 85.52, b = 148.50, c = 93.82 Å, β = 99.82°. The diffraction of the crystals extended to 2.56 Å resolution. The asymmetric unit contained two MEDI4893 Fab–AT complexes. This corresponds to a crystal volume per protein weight (VM) of 2.3 Å3 Da−1 and a solvent content of 47%. The three‐dimensional structure of this complex will contribute to an understanding of the molecular basis of the interaction of MEDI4893 with AT. It will also shed light on the mechanism of action of this antibody, the current evaluation of which in the field of S. aureus‐mediated diseases makes it a particularly interesting case study. Finally, this study will provide the three‐dimensional structure of AT in a monomeric state for the first time.